2010
DOI: 10.1103/physreve.82.031303
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric velocity correlations in shearing media

Abstract: A model of soft frictionless disks in two dimensions at zero temperature is simulated with a shearing dynamics to study various kinds of asymmetries in sheared systems. We examine both single particle properties, the spatial velocity correlation function, and a correlation function designed to separate clockwise and counter-clockwise rotational fields from one another. Among the rich and interesting behaviors we find that the velocity correlation along the two different diagonals corresponding to compression a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…27 However this model is less realistic and leads to anomalous results for the fluctuations and their spatial correlations. 2,3,28 The shear stress s is calculated from the contact forces via the Born-Huang formula: 29…”
Section: Numerical Modelmentioning
confidence: 99%
“…27 However this model is less realistic and leads to anomalous results for the fluctuations and their spatial correlations. 2,3,28 The shear stress s is calculated from the contact forces via the Born-Huang formula: 29…”
Section: Numerical Modelmentioning
confidence: 99%
“…Thus, detailed studies of the link between statistics and spatial structures are left for future. Similarly, anisotropy induced by shear [93][94][95][96][97][98][99], e.g. shear-bands, should be examined in future.…”
Section: B Future Workmentioning
confidence: 99%
“…Olsson [42] reported that the computational calculation to obtain the correlation length and resolve its scaling behavior is an arduous numerical task; he further comments that the two-point correlation associated with non-affine velocity for a system under shear presents zones of correlation and anticorrelation associated with the angular orientation in which the correlation is measured. Therefore to avoid anticorrelation effects in the orientation dynamics, we propose to measure the correlation using the spatial activity field of the non-affine velocity, defined as…”
mentioning
confidence: 99%